Qlik Sense Cookbook : Over 80 recipes on data analytics to solve business intelligence challenges, 2nd Edition /: Over 80 recipes on data analytics to solve business intelligence challenges, 2nd Edition. (2018) - Labbe, Pablo; Hand, Philip; Kharpate, Neeraj
No abstract available